2012
DOI: 10.1111/ene.12015
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and prognostic impact of comorbidities in amyotrophic lateral sclerosis

Abstract: Persons with cardiovascular diseases or risk factors seem to be at lower risk of ALS. Although these diseases are apparently somehow protective regarding ALS susceptibility, their presence did not modify disease progression and survival in patients with ALS. Our study further confirms the well-known continuum between ALS and dementia. It also suggests a link with other neurodegenerative diseases such as Parkinson's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
76
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 44 publications
9
76
3
Order By: Relevance
“…ALS patients had a significantly lower BMI than controls, similar to other studies [16], in line with metabolic changes and substantial weight loss observed in ALS patients. While there is evidence suggesting that ALS patients may be less likely than the general population to have cardiovascular disease and cardiovascular risk factors [17], no such difference was observed in our population between prevalent ALS patients and controls. The significantly lower prevalence of CKD among ALS patients compared to controls in our study is similar to a previous study, which found an odds ratio of 0.32 (95% CI 0.18-0.57) for ALS patients compared to age- and sex-matched controls [18].…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…ALS patients had a significantly lower BMI than controls, similar to other studies [16], in line with metabolic changes and substantial weight loss observed in ALS patients. While there is evidence suggesting that ALS patients may be less likely than the general population to have cardiovascular disease and cardiovascular risk factors [17], no such difference was observed in our population between prevalent ALS patients and controls. The significantly lower prevalence of CKD among ALS patients compared to controls in our study is similar to a previous study, which found an odds ratio of 0.32 (95% CI 0.18-0.57) for ALS patients compared to age- and sex-matched controls [18].…”
Section: Discussioncontrasting
confidence: 77%
“…In comparison, other countries report a median survival from onset to death ranging from 20 to 48 months, with 10-20% of patients surviving more than 10 years from diagnosis [1]. Median survival times measured from ALS symptom onset are approximately 1 year longer than from ALS diagnosis [17,20,21,22,23,24]. Older age (≥40 years) of onset and bulbar (compared to limb) onset are associated with poorer prognosis [1,24].…”
Section: Discussionmentioning
confidence: 99%
“…One case-control study showed no significant difference in the frequency of a range of broad disease categories (including endocrine). 8 In a cohort of 514 patients with ALS, 9 the prevalence of cardiovascular diseases and cardiovascular risk factors was significantly lower than their prevalence in the general population, confirming previously published findings (discussed in reference 10). Autoimmunity in the pathogenesis of ALS, or perhaps as a mediator of heterogeneity, has long been postulated.…”
supporting
confidence: 85%
“…Besides FTD, the comorbidity of ALS with other neurodegenerative disorders, such as Parkinson disease, may also contribute to the association between previous depression and increased risk of ALS. 15 Finally, little research has been done regarding the potential psychological stress experienced by patients with ALS between the first symptom onset and the final diagnosis, an interval of 1 year on average. 16 Depression may therefore also be a result of the psychological distress experienced during the progressive symptom development and the often stressful diagnostic workup before ALS diagnosis.…”
Section: Discussionmentioning
confidence: 99%